Objects and implementation of environmental and economic reengineering of technogenic dangerous oil and gas - Степанюк, Г. С. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
Increasing environmental problems in the functioning and management of oil and gas companies prove the necessity and feasibility of the introduction of advanced management technologies of production greening. One such technology is the re-engineering of business processes and due to priorities of solving environmental problems in oil and gas business reorganization proposed new direction changes - ecological and economic re-engineering. The main objects of ecological and economic reengineering are analyzed and classified. Based on this classification it is determined that the proposed management technology projects can be of two types, namely internal reengineering projects (industrial purposes, focused on the safe production, pollution prevention projects, i.e. projects on environmental protection) and external reengineering projects, concerning separated from the oil and gas companies servicing units (transport, maintenance, energy, accounting, engineering diagnostics, etc.). Based on the example of OGPD "Dolynanaftogas" the possible environmental and economic reengineering projects targeted imperfect production processes are proposed.